2003
DOI: 10.1038/sj.npp.1300235
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of the 5-HT1B Receptor in Spatial and Aversive Learning in the Rat

Abstract: The present study examined the role of the 5-HT 1B receptor in learning and memory. The ability of the 5-HT 1B receptor agonist anpirtoline and the selective 5-HT 1B receptor antagonist NAS-181 to affect spatial learning in the water maze (WM) and aversive learning in the passive avoidance (PA) task were examined in the rat. Anpirtoline (0.1-1.0 mg/kg, s.c.) caused a dose-dependent impairment of learning and memory in both the WM and PA tasks. NAS-181 (1.0-10 mg/kg, s.c.) failed to alter performance of the WM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 79 publications
2
18
0
Order By: Relevance
“…The even 5-HT 1B R distribution found across the molecular layer is also suggestive of localisation to granule cell processes which innervate throughout. Further investigation is required to identify the neurotransmitters present within 5-HT 1B R positive terminals as it is possible that some of these are the cholinergic terminals identified in other studies (Ahlander-Luttgen et al, 2003;Hu et al, 2007;Maura and Raiteri, 1986;Rutz et al, 2006;Wolff et al, 2003a,b).…”
Section: -Ht 1b Rs Are Absent From Gabaergic Interneuronsmentioning
confidence: 95%
See 1 more Smart Citation
“…The even 5-HT 1B R distribution found across the molecular layer is also suggestive of localisation to granule cell processes which innervate throughout. Further investigation is required to identify the neurotransmitters present within 5-HT 1B R positive terminals as it is possible that some of these are the cholinergic terminals identified in other studies (Ahlander-Luttgen et al, 2003;Hu et al, 2007;Maura and Raiteri, 1986;Rutz et al, 2006;Wolff et al, 2003a,b).…”
Section: -Ht 1b Rs Are Absent From Gabaergic Interneuronsmentioning
confidence: 95%
“…Despite a focus on links between serotonergic and cholinergic transmitter systems (Ahlander-Luttgen et al, 2003;Hu et al, 2007;Rutz et al, 2006;Wolff et al, 2003a,b), modulation of glutamatergic currents has also been demonstrated in a variety of brain regions (Bouryi and Lewis, 2003;Lemos et al, 2006;Li and Bayliss, 1998;Muramatsu et al, 1998). Here, it is thought that 5-HT 1B R activation exerts an effect through pre-synaptic mechanisms, predominantly via action as inhibitory auto-and/or heteroreceptors, thereby modulating neurotransmitter release (Sari, 2004).…”
mentioning
confidence: 93%
“…Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by learnmem.cshlp.org Downloaded from solidation, and retrieval may be impaired by 5-HT 1A or 5-HT 1B (Ahlander-Luttgen et al 2003) receptor stimulation, whereas blockade of 5-HT 1A or 5-HT 2A/2B/2C receptors has no effect. 5-HT 3 antagonists or 5-HT 4 agonists (systemic or central) improved PA learning and/or prevented scopolamine-or hypoxic-induced amnesia.…”
Section: Learning and Memory 369mentioning
confidence: 99%
“…Operant autoshaping-task mice lacking 5-HT 1A or 5-HT 1B receptors learn faster than do wild-type mice (Pattij 2002), but 5-HT 1A KO mice showed deficits in hippocampal-dependent learning and memory tests (Sarnyai et al 2000). 5-HT 1B KO mice showed WM enhanced-platform acquisition and probe trial performance (Buhot et al 2000), and selective 5-HT 1B antagonists facilitated WM (Ahlander-Luttgen et al 2003) and autoshaped memory (Table 3). In parallel to the finding that 5-HT 2B/2C receptor antagonist (Table 3) had no effect on autoshaped memory, 5-HT 2C receptor KO mice showed normal hidden-platform and preference for the target quadrant during a probe trial.…”
Section: Related Findings: Wm and Pamentioning
confidence: 99%
“…1)] is a high-affinity antagonist at both the serotonin (5-HT) 5-HT 1A and 5-HT 1B receptors that was developed for the treatment of cognitive impairment in Alzheimer's disease. As antagonists at the 5-HT 1A and 5-HT 1B receptors have been found to enhance learning and memory through independent mechanisms in animal models (Åhlander-Lüttgen et al, 2003;Ögren et al, 2008), our project was initiated based on the hypothesis that antagonism at both these receptors may provide more efficacious pharmacologic treatment than a compound selective for any of the receptors.…”
Section: Introductionmentioning
confidence: 99%